PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK PESERTA DIDIK - Muhammad Satuman Ali (UNISAN JURNAL, 2024)
This examination plans to decide the job of Islamic Strict Training (PAI) educators in creating understudy ethics at Muzammil Al Aziziyah Private Professional School. The exploration technique utilized is subjective with a contextual investigation approach. Information assortment was helped out through inside and out interviews with PAI educators, study hall perceptions, and examination of records connected with the educational program and school exercises. The exploration results show that PAI instructors impact understudies' moral and character improvement. PAI instructors not just go about as educators who convey strict material, yet additionally as good examples, coaches and moral chiefs for understudies. They show conduct that is as per Islamic strict qualities in day to day existence, give inspirational support, and give counsel and direction to understudies in managing different moral circumstances. Inventive and intuitive showing approaches are additionally used to expand understudies' comprehension and acknowledgment of strict qualities and ethical quality. In this unique situation, the job of PAI educators at Muzammil Al Aziziyah Private Professional School is vital in molding understudies' personality and ethics. With the solid and successful job of PAI educators, it is trusted that the objective of value character training in schools can be accomplished. Nonetheless, there should be more prominent help and acknowledgment from instructive establishments and the public authority for the job of PAI educators in endeavors to prepare understudies' personality and ethics. Hence, the aftereffects of this exploration give a significant commitment to how we might interpret the significant job of PAI educators in character training in professional secondary schools.